The ethical imperative to honor autistic clients’ autonomy in mental health treatment - McVey, Alana J.; Glaves, Katherine Jo; Seaver, Samantha; Casagrande, Karís A. (Frontiers in Psychiatry, 2023)
Autistic adolescents and adults commonly experience mental health concerns; however, mental health clinicians may hold implicit stigmatizing views of autism that contribute to case conceptualization and treatment goal setting that aligns more with caregivers’ than clients’ goals. This impingement on client autonomy is concerning, problematic, and potentially harmful for autistic clients who are of an age to set their own treatment agenda regardless of co-occurring intellectual disability and/or language delays. An application of the shared decision-making framework, an evidence-based tool for promoting client autonomy, can help to avoid these challenges in treatment. In this perspective, we use a case vignette as an anchor for discussing the imperative of honoring autistic clients’ autonomy in mental health treatment and guiding shared decision-making to reduce stigma, promote autonomy, and increase collaborative care for autistic clients in mental health treatment.